Transformation and Innovation in Islamic Economics: Responding to Challenges in the Digital and Globalization Era - Siti Ahdina Saadatirrohmi; Pramudi Harsono; Asri Ady Bakri (Journal of Islamic Economy, 2024)
The Islamic economy has undergone significant development in recent decades, especially with the digital transformation and globalization affecting various economic sectors. These changes bring new challenges to the sharia economy, but they also open up opportunities for innovation and increased relevance. This research aims to analyze how digital transformation and innovation can help the Islamic economy overcome challenges in the modern era. With the Systematic Literature Review (SLR) approach, this study identifies various strategies and practices that have been implemented to improve the competitiveness of the sharia economy in the midst of global changes. The results of the study show that the integration of digital technology, such as sharia fintech and blockchain, is one of the important factors in encouraging the efficiency and transparency of sharia economic transactions, especially in the context of the global market. In addition, increasing Islamic financial literacy is also the key to ensuring that the public understands and can access financial products in accordance with sharia principles. International collaboration is also needed to create a more inclusive and sustainable sharia economic ecosystem. Overall, this study emphasizes that adaptation to digital technology and increased global collaboration are important steps in maintaining the relevance of the sharia economy in the era of increasingly digital and globalization